Using Traditional Knowledge in Economic Development : The Impact of Raised Field Irrigation on Agricultural Production in Puno, Peru - Middleton, Melisande (World Bank, Washington, DC, 2012)
The Andean region of Puno, known as the altiplano, is located at 3,830 meters above sea level. The terrain is prone to flooding, and thus difficult to cultivate. In order to deal with this situation, Andean indigenous populations displaced huge amounts of soil in order to create raised fields that were better adapted to agricultural use. Raised fields resolved many of the problems that affect agriculture at high altitude. The technology combines the rehabilitation of marginal soils, drainage improvement, increased water storage, more efficient use of radiant energy, and attenuation of the effects of frosts. The raised platform allows farmers to double the depth of topsoil for crops, and provides dry surfaces in the wet and often flooded lake and river terrain.